Konsep Tadris Ekonomi di Dalam Al-Qur’an - Hikmatullah Jamud (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2017)
Since humans are born on earth he will always try to maintain their existence and function as khalifah. To realize all that God has provided resources (resources and facilities) of life that can be accessed by humans in meeting needs such as food and clothing, security and improving the standard of economic life. Therefore humans are required to develop production and distribution processes that are supported by the development of economic systems, communication and information systems. As a provision to maintain human existence, manhaj al-hayat and wasilatul Hayat were given. Manhaj Hayat is all the rules of human life that are sourced from the Qur'an and Assunnah. And We send down to you Al-Kitab (Al-Quran) to explain everything and instructions and grace and good news for those who surrender "( QS: 16:89 (and remember) the day (when) We raise up for each of the people a witness over them of their own and We bring you (Muhammad) as a witness of all mankind, and We send down to you the Book (Al-Quran) to explain everything and instructions as well as grace and good news for people who surrender, In another verse, Allah SWT said: While the meaning of wasilatul hayah is air, water, plants, livestock, and property. others who are useful in life. He is Allah, Who made all that is on earth for you and He willed (created) the heavens, then made seven heavens, and He is the All-knowing of all things. ". One of the economic systems described by the Qur'an is the story of the Prophet Yusuf (as). Joseph said: "So that you plant seven years (forever) as usual; then what you harvest, you should let it turn aside except for a little for you to eat. Then after that seven very difficult years will come, which spends what you save to deal with it ( difficult year), except for a little bit of (wheat germ) that you keep. Then after that, there will come a year in which humans will be given rain (sufficiently) and in that period they will squeeze wine. " Al-Dumuhi said the role played by Yusuf was the same as the obligation that should be carried out by the minister of finance, economy, trade and agricultural development planning. At present, as for the objectives to be achieved from the economic policies taken by the Prophet Yusuf AS are food self-sufficiency and the fairness of the consumption and distribution process by way of concern for the agricultural sector to increase production. This paper aims to prove that the Qur'an regulates various problems in human life including economics not as expressed by western thinkers. Islam is an obstacle to economic growth (Islam is a barrier to economic growth).